Exploring the in vitro and in vivo anticancer activity of lasiokaurin on nasopharyngeal carcinoma - Huanhuan Pu; Jinrong Lin; Li-Sha Shen; Yu-Shan Lin; Rui-Hong Gong; Guo Qing Chen; Sibao Chen (Elsevier, 2023)
Objective: To evaluate the anticancer activity of the natural diterpenoid lasiokaurin (LAS) against nasopharyngeal carcinoma (NPC) both in vitro and in vivo, along with investigating its underlying mechanism. Methods: MTT and colony formation assays were used to assess cell viability. Flow cytometry was utilized for the analysis of cell cycle arrest and apoptosis. Additionally, wound healing and transwell invasion assays were conducted separately to investigate cell migration and invasion. To uncover potential targets and pathways of LAS within NPC, a network pharmacological study based on RNA-sequencing (RNA-seq) was performed. Immunoblotting was subsequently used to determine protein levels. Furthermore, the anti-NPC activity of LAS was evaluated in vivo using a xenograft mouse model. Results: Based on in vitro investigations, it is evident that LAS exerted substantial inhibitory effects on NPC cells. Notably, LAS demonstrated significant reductions in cell viability, migration, and invasion capabilities, while simultaneously inducing apoptosis and G2/M cell cycle arrest. Furthermore, LAS suppressed the activation of MAPK, mTOR, STAT3, and NF-κB pathways within NPC cells. Additionally, in vivo experiments underscored LAS's capacity to attenuate NPC tumor growth without eliciting any discernible impact on body weight. Conclusion: Our data clearly demonstrate the anticancer activity of LAS against NPC, both in vitro and in vivo. These findings firmly position LAS as a potential candidate for the treatment of NPC.